Legacy of land-cover changes on soil microbiology in Burgundy vineyards (Pernand-Vergelesses, France) - Quiquerez, Amélie; Garcia, Jean-Pierre; Dequiedt, Samuel; Djemiel, Christophe; Terrat, Sébastien; Mathieu, Olivier; Sassi, Audrey; Ranjard, Lionel (OENO one, 2022)
Present-day soil physicochemical characteristics, land use/land cover (LULC), and field management practices are commonly recognised as the main drivers shaping archaeal/bacterial and fungal communities in vineyard soils. Few studies have investigated the legacy of past land uses on soil microbial biodiversity, yet anthropogenic disturbances have already been proven to affect soil characteristics over decades. In this study, we explore the possibility of long-lasting impacts of forest-to-vineyard conversion on present-day soil archaeal/bacterial and fungal communities after 15 years of vine cultivation. The selected study area is in a Burgundian vineyard (Pernand-Vergelesses, Burgundy, France), where it was possible to reconstruct the history of land cover and land use for the past 40 years. Soil samples were collected from five zones managed under similar pedo-climatic conditions but with different land-use histories (a 70-year-old vineyard, a 15-year-old vineyard converted from pine forest, a 15-year-old vineyard converted from mixed forest, a pine forest and a mixed forest). For each zone, basic physicochemical parameters (organic carbon, total nitrogen, copper, C:N ratio, and soil texture) were measured, and DNA was extracted to characterise the microbial biomass, and also the richness and taxonomic composition of archaeal/bacterial and fungal communities (16S and 18S). Our results show that changes in LULC lead to differential responses in soil microbial biomass, and in archaeal/bacterial and fungal richness and taxonomic composition. After 15 years of cultivation, the present-day microbial biomass and indigenous archaeal/bacterial communities of recent vineyard soils are shown to be partly inherited from past LULC, but no evidence was found of long-term impacts of past land use on fungal communities. Past land-use history should therefore be added to the well-established set of environmental drivers, providing valuable information to explain the spatial variability of soil microbiology, observed at intra-plot, plot, and landscape scales. Integrating the history of changes in LULC is therefore recommended to evaluate and adopt the best strategies to develop sustainable management practices.